(untitled) (Communications in Inorganic Synthesis, 2015)
Abstract: Ni nanoparticles (Ni-NPs) have been prepared from an inorganic precursor by thermal decomposition route. The prepared precursor Ni(C9H7O2)2(N2H4)2 was characterised by hydrazine and metal analyses, infrared spectrum and thermo gravimetry. By the thermal treatment of the precursor under suitable conditions, Ni-NPs of average size around 23 nm were obtained. Nanostructured Ni particles thus synthesised were characterised by X-Ray Diffraction (XRD), High Resolution Transmission Electron Microscopic (HRTEM), Selected Area Electron Diffraction (SAED) and Scanning Electron Microscopic (SEM) techniques.